Harmonious Interaction Between Learners and Educators - Ode Yahyu Herliany Yusuf; Asti Asti; Mayank Septia Ningsi; Safiana Safiana; Wa Ode Amira Fahrani (CV. Rayyan Dwi Bharata, 2023)
Interaction is always related to the terms of communication and relationship. Communication means interacting with something. The elements involved in communication aim to determine harmonious interactions in the learning process so that they can improve children's learning achievements. Teachers are also invited to carry out effective communication so that they can provide educational messages to children without any pressure. Thus, the teacher's knowledge of the child-teacher relationship increases, and the teacher can build the relationship in the exact plan he can.